Crop diversity, climate change adaptation and resilience: good practice cases from Africa - Vernooy, Ronnie; Adokorach, Joyce; Wasswa Mulumba, John; Mushita, Andrew; Wahome, Patrick (Climate Change, Agriculture and Food Security (CCAFS), 2021)
Across Africa, erratic and less predictable rainfall, higher temperatures, heat spells, and recurring droughts are predicted to become more frequent. This is leading to a change of cropping seasons and growing cycles and occurrence of new pests and diseases. As a result of these irregularities and uncertainties, farmers can no longer rely on crops and crop varieties that used to do well, with negative impacts on nutrition and food security and the capacity of farmers to withstand shocks. One strategy to face this new reality, is to create better access to crop and varietal diversity. Increased access to inter and intracrop genetic diversity could give farmers an opportunity to switch to crops that are more resilient under new conditions, e.g. a switch from maize to millet in rain-stressed areas. Farmers could also switch to varieties of the same crop that are better adapted to their local situation. However, the potential of local diversity is not always well understood, and with rural populations becoming older and youth migrating to urban areas, knowledge on agrobiodiversity is disappearing.
Keywords: Crop diversity; Climate change adaptation; Resilience; Practice cases; Africa